Whole Genome Sequencing Links Mycobacterium bovis From Cattle, Cheese and Humans in Baja California, Mexico - Ortiz, Alejandro Perera; Perea, Claudia; Davalos, Enrique; Velázquez, Estela Flores; González, Karen Salazar; Camacho, Erika Rosas; García Latorre, Ethel Awilda; Lara, Citlaltepetl Salinas; Salazar, Raquel Muñiz; Bravo, Doris M.; Stuber, Tod P.; Thacker, Tyler C.; et al. (Frontiers in Veterinary Science, 2021)
Mycobacterium bovis causes tuberculosis (TB) in cattle, which in turn can transmit the pathogen to humans. Tuberculosis in dairy cattle is of particular concern where the consumption of raw milk and dairy products is customary. Baja California (BCA), Mexico, presents high prevalence of TB in both cattle and humans, making it important to investigate the molecular epidemiology of the disease in the region. A long-term study was undertaken to fully characterize the diversity of M. bovis genotypes circulating dairy cattle, cheese, and humans in BCA by whole-genome sequencing (WGS). Tissue and cheese samples were collected in BCA over a two-year period and sent to the laboratory for mycobacterial culture, histology, direct PCR, and WGS. A total of 445 and 314 tissue and cheese samples, respectively, were collected. For tissue, isolation was positive for 86.8%, direct PCR detection was 90%, and histology confirmed 85.9% as mycobacteriosis-compatible. For cheese, the isolation rate was 2.5% and PCR detected 5.7%. Overall, there was agreement between diagnostic tests. Subsequently, a total of 345 whole-genome sequences were obtained; and phylogenetic analysis placed these isolates in 10 major clades. Single nucleotide polymorphism (SNP) analysis revealed putative transmission clusters where the pairwise SNP distance between isolates from different dairies was ≤ 3 SNP. Also, human and/or cheese isolates were within 8.45 (range 0-17) and 5.8 SNPs (range 0-15), respectively, from cattle isolates. Finally, a comparison between the genotypes obtained in this study and those reported previously showed that full characterization of the genetic diversity of M. bovis in the region was achieved. In conclusion, WGS provided evidence of ongoing local transmission of M. bovis among the dairies in this high-TB burden region of BCA, as well as close relationships between isolates from humans, cheese, and these cattle. This confirms the need for a coordinated One Health approach in addressing the elimination of TB in animals and humans.